Molecular docking and ADME profiles of β-carboline analogues as potential antibiotic agents targeting DNA gyrase - Abdul Aziz, Ahmad Amzar; Aminudin, Nurul Iman; Pungot, Noor Hidayah; Hamzah, Nurasyikin (2023)
Antibiotic resistance remains a major human threat worldwide, owing to bacteria and fungi's ability to mutate over time, as well as a dramatic decline in the antibiotic pipeline. Plants can produce a variety of bioactive secondary metabolites and beneficial for future antibiotic discovery. Herein, using in-silico approaches, an in-house library of 20 β-carboline analogues was virtually screened to evaluate their antibiotic activities and drug-likeness properties. The molecular docking using DNA gyrase crystal structure (PDB ID: 1AJ6) showed that 19 derivatives bind strongly to the target protein (in a range of - 6.8 kcal/mol to -9.4 kcal/mol) except 1o (-6.7 kcal/mol) which exhibited comparable binding energy to the reference drug, novobiocin (-6.8 kcal/mol). Of these, derivatives 1l bind strongest (-9.4 kcal/mol) mainly due to the hydrogen bond interactions that occur between the carboxylic acid moiety and secondary amine with Val71 and Asp73 residues, respectively. ADME profiling predicted that almost all β-carboline analogues demonstrated favourable drug-likeness properties and bioavailability profiles, suggesting their potential DNA gyrase inhibitors. Thus, through this work, the derivatives of β-carboline may serve as a starting point for the development of effective antibacterial medications through further modification and optimisation process.